أثر آليات حوكمة الشركات على جودة التقارير المالية - عيدود، محمد; بن ديلمي ،اسماعيل (جامعة الوادي University of Eloued, 2025)
The purpose of this study is to ascertain how corporate governance practices affect the production of highquality financial reports. We employed the descriptive technique, depending on the questionnaire instrument, to accomplish the study's goals and test the hypotheses. The statistical software SPSS26 was utilized to process and analyze the questionnaire. The following conclusions were drawn from this investigation. The Algerian Electricity and Gas Distribution Company does not actually commit to implementing corporate governance mechanisms; the lack of transparency and credibility is reflected in the quality of financial reports. Governance mechanisms have a positive impact on the quality of financial reports issued by the Electricity and Gas Distribution Company.
The impact of corporate governance mechanisms on the quality of financial reports The case of the electricity and gas distribution company
مقال
Keywords: حوكمة الشركات; التقارير المالية; الإفصاح المالي; جودة التقارير المالية; corporate governance; financial reports; financial disclosure; financial reporting quality